2017
DOI: 10.22271/ortho.2017.v3.i3p.170
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological profile of post-traumatic osteomyelitis in tertiary hospital in Yaoundé –Cameroon

Abstract: Background: Post-traumatic osteomyelitis is bone infection secondary to a trauma (open fracture or bone surgery). It is a painful and frustrating disease characterised by a high rates of therapeutic failures and a costly management. However, treatment is increasingly becoming difficult because of the phenomenon of antibiotic resistance. The present study was realised to determine the epidemiological and susceptibility profile of bacterial isolates in posttraumatic osteomyelitis in a tertiary hospital in the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…The femur was the highest bone involved in infections accounting for 8 cases (42.11%). These results do not correlate with those obtained from studies conducted in Cameroon in 2005 and 2017 [3,4] in which the tibia was reported as the highest bone involved in osteomyelitis (34.8%) and post-traumatic osteomyelitis (48.4%). Another study conducted in Mali in 2008 [5] reported the tibia as the most frequent (38.03%) bone in lower limb osteomyelitis followed by the femur (35.21%).…”
Section: Clinical Profilecontrasting
confidence: 93%
“…The femur was the highest bone involved in infections accounting for 8 cases (42.11%). These results do not correlate with those obtained from studies conducted in Cameroon in 2005 and 2017 [3,4] in which the tibia was reported as the highest bone involved in osteomyelitis (34.8%) and post-traumatic osteomyelitis (48.4%). Another study conducted in Mali in 2008 [5] reported the tibia as the most frequent (38.03%) bone in lower limb osteomyelitis followed by the femur (35.21%).…”
Section: Clinical Profilecontrasting
confidence: 93%
“…As a result, patients with FRI in closed trauma have high morbidity rates and are less likely to return to duty. The increasingly frequent use of internal fixation and the emergence of antibiotic resistant microorganisms have exacerbated this problem [3].…”
Section: Introductionmentioning
confidence: 99%